Telemedicine in Cancer Pain Management: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 3 (27th August 2022) - Buonanno, Pasquale; Marra, Annachiara; Iacovazzo, Carmine; Franco, Massimo; De Simone, Stefania
Abstract: Objective: Telemedicine is defined as the delivery of medical services through a variety of telecommunication tools. This novel approach can fit the needs of cancer patients who cannot often reach clinics due to their disabling symptoms. In this population of patients, pain is undoubtedly the most important symptom which dramatically affects the quality of life. Our work aimed to investigate the effectiveness of telemedicine in the management of cancer pain in order to assess the feasibility of a combination between telemedicine and traditional in-person visits; we also propose a model of integration of these two approaches. Methods: We followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to conduct our study. Quality assessment and risk of bias were performed according Cochrane criteria. Results were reported as mean differences and summarized using forest plots. We performed a trial sequential analysis (TSA) to assess the conclusiveness of our results. Results: Pain severity score and pain interference were lower for patients treated with telemedicine compared to those undergoing classical management (mean difference: −0.408; P  =< .001 and −0.492; P  = .004, respectively). TSA confirmed that our results were statistically significant and pointed out the need of other studies to reach the required sample size. PROSPERO registration: CRD42022333260. Conclusions: Telemedicine can be effectively used to manage cancer pain. This novel approach will certainly have a revolutionary economic and organizational impact on health care systems in the next future. Furthermore, the model herein proposed could help set up an algorithm to safely and efficiently implement telemedicine.